Características demográficas e sócio-ocupacionais dos migrantes nascidos nos países do Cone Sul residentes no Brasil - Gabriela Adriana Sala (2005)
In the decades prior the 2000 Demographic Census, the composition of the population from Mercosur and Associated States, resident in Brazil, changed. This process gives rise to a series of questions about immigrants demographic, educational, labor and wage characteristics and about differences between them and Brazilian workers.This thesis estimates migratory balances for immigrants born in Argentina, Bolivia, Chile, Paraguay and Uruguay in the eighties and nineties, for Brazil, as a whole, and for the Brazilian states that concentrated the largest proportions of population of these immigrants. It also analyzes some demographic characteristics from these populations that allow detecting processes of population aging and feminization, between 1980 and 2000.This thesis analyzes the educational changes of the cohorts of immigrants from Argentina, Bolivia, Chile, Paraguay and Uruguay, determined by the year that they established their residence in Brazil. It also estimates the magnitude of the presence and the characteristics of Brazilian South Cone qualified immigrants. It presents two typologies of the South Cone workers, for each sex, following a multidimensional approach, based on the Grade of Membership (GoM) method.It also estimates the immigrant workers concentration and segregation levels, according to job and sectors of economic activity, comparing them with workers born in Brazil. By using different wage equations, it compares indicators that relate human capital and economic performance from South Cone immigrants to Brazilian workers. In order to capture expressions of wage discrimination, this work measures native and immigrant workers incomes differentials through the Oaxaca decomposition.